Optimising ventilation for thermal comfort and infection control in vehicles: A review on CFD applications and techniques - Tan, Kai Ying; Wong, Sien Jie; Tan, Huiyi; Kek, Hong Yee; Mohd Hafiz Dzafan, Othman; Wong, Syie Luing; Mohamad Nur Hidayat, Mat; Fong, Yi Ka; Wong, Keng Yinn (Penerbit UTM Press, 2025)
Effective ventilation in vehicles is crucial for ensuring thermal comfort and controlling airborne infections. This review focuses on the application of Computational Fluid Dynamics (CFD) in optimising vehicle ventilation systems. It examines various CFD methodologies, including turbulence models, meshing techniques, and solver algorithms, as well as their impact on ventilation performance. The review highlights that RNG k-ε and SST k-ω are among the most commonly used turbulence models in vehicle cabin simulations, based on their suitability for modelling complex airflow patterns and their validation against measured data. It also examines meshing techniques that influence the reliability of CFD simulations, including structured, unstructured, and hybrid meshes. This review article also discusses solver algorithms and their role in efficiently solving the governing equations of fluid flow and heat transfer. Various CFD approaches have been employed to reduce the risk of particle transmission by improving airflow distribution and contaminant removal effectiveness. Moreover, CFD has been used to enhance thermal comfort by optimising temperature distribution and managing heat loads. By synthesising recent advancements and case studies, this review provides valuable insights for researchers and practitioners, aiming to enhance ventilation systems in vehicles through advanced CFD techniques. This work aligns with Sustainable Development Goal (SDG) 3 (Good Health and Well-Being), by improving air quality and reducing infection risks, and SDG 11 (Sustainable Cities and Communities), by contributing to safer and more comfortable transportation solutions. The integration of CFD into vehicle ventilation optimisation supports the creation of healthier and more efficient transportation systems, ultimately contributing to broader sustainability goals.